Inkjet Printing Based Layer‐by‐Layer Assembly Capable of Composite Patterning of Multilayered Nanofilms. Issue 12 (10th November 2017) - Choi, Moonhyun; Heo, Jiwoong; Choi, Daheui; Hwangbo, Sunghee; Hong, Jinkee
Abstract: Surface modification involves developing a versatile thin film by combining the physical, chemical, or biological characteristics of the functional materials and can facilitate controlling material for desirable aims. Layer‐by‐layer (LbL) assembly can be used to create materials with controlled thicknesses and morphologies, diverse functionalities, and unique structures on any surface. However, despite the advantages of the LbL fabrication technique, there are limits to its application because it is a time‐consuming process and has difficulty controlling the shape of nanofilms. In addition, controlling the lateral organization is difficult because the preparation methods are based on one‐pot self‐assembly. In this study, a multilayered fabrication system is developed for the high‐throughput LbL assembly of nanofilms through inkjet printing. With various types of materials from synthetic polymer to graphene oxide to natural polymer and protein, the approach can tune the preparation of nanoscale multilayers with desired structures and shapes for specific applications on various substrates, including a silicon wafer, quartz glass, and cellulose‐based paper. Abstract : Multilayered nanofilms with various functional materials (synthetic and natural polymer, protein, and graphene) are fabricated by integrating layer‐by‐layer assembly and inkjet printing. Thickness, roughness, combinations, structures, and shapes of the nanofilms are desirably controllable. In addition, the printed nanofilms are deposited on several substrates ranging from silicon wafer to paper.